Titanium oxide film catalytic material for quickly synthesizing imine at high yield as well as preparation method and application of titanium oxide film catalytic material
By regulating the layer spacing and titanium oxygen atom ratio of titanium oxide film catalytic materials, two-dimensional nano-domain confined channels and photoexcited reactive oxygen species are provided, which solves the existing problems of long photocatalytic reaction time and low yield, and achieves rapid and high yields The imine synthesis simplifies the process and reduces environmental pollution.
Patent Information
- Application Number
- CN202411622792.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The existing photocatalytic reaction based on titanium dioxide has problems such as long reaction time, low yield, oxygen atmosphere and heating, and it has caused pollution to the environment, making it difficult to achieve rapid and high yield synthesis of imine.
Develop a titanium oxide film catalytic material to provide a synergistic catalytic effect of two-dimensional nano-domain confined channels and photoexcited reactive oxygen species by regulating layer spacing and titanium-oxygen atomic ratio to achieve rapid and high-yield catalytic imine synthesis, using continuous mobile phase Reaction method, simplify the separation and purification process.
It realizes rapid (0.1-100s) high yield (70-100%) synthesis of imine without additional heating and oxygen atmosphere, simplifies the separation and purification process, reduces environmental pollution, and conforms to the concept of green chemistry.
Smart Images

Figure CN119140080A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a titanium oxide film catalytic material with adjustable interlayer spacing, adjustable thickness and adjustable excitation light intensity, a preparation method thereof and application in photocatalytic preparation of imines, belonging to the field of film catalytic materials and technology. Background Art
[0002] Imine is an important intermediate in the fields of medicine, agriculture, and synthesis, and can be further used in the synthesis of quinolones, cucurbiturils, oxygen-nitrogen heterocycles, and other substances. 1 C=NR 2 , is a class of organic compounds formed when the oxygen atom on the carbonyl group is replaced by nitrogen. The typical method for preparing imines is through the condensation reaction of primary amines and aldehydes. The reaction mechanism is that the lone pair of electrons of the amine first attacks the carbonyl group to undergo a nucleophilic addition reaction to obtain a hemiaminal (-C(OH)(NHR)-) intermediate, and then continues to eliminate a molecule of water to obtain the imine. However, since the reaction equilibrium is more inclined to the side of the carbonyl compound and the amine, the reaction process requires azeotropic distillation, reflux water separation, or the use of a dehydrating agent (such as molecular sieves or concentrated sulfuric acid) to shift the equilibrium toward the formation of imine compounds.
[0003] Photocatalytic coupling of benzylamine compounds to prepare imines provides a new technical path for the preparation of imines. As a typical photocatalyst, titanium dioxide (such as commercialized P25) has been widely used in various fields such as food, medicine, and cosmetics. Under the irradiation of light, the electrons and holes in titanium dioxide are separated to form active oxygen species, which promote the coupling of benzylamine compounds. However, the current photocatalytic reaction based on titanium dioxide has problems such as long reaction time (>6 hours), low yield (<49%), oxygen atmosphere (>1atm oxygen) or heating (>60°C), and large amount of catalyst. While consuming a large amount of reagents and time, it will also cause serious pollution to the environment, which is not in line with the concept of green chemistry. Summary of the invention
[0004] In order to improve the deficiency of the prior art that it is impossible to achieve rapid and high-yield synthesis of imines, the present invention provides a titanium oxide film catalytic material for photocatalytic synthesis of imines, and a preparation method and use thereof. The titanium oxide film catalytic material has a continuously adjustable interlayer spacing while retaining the titanium oxide nanosheet structure, and achieves rapid and high-yield catalytic synthesis of imines through the synergistic catalytic effect of the two-dimensional nano-confined channels provided by the titanium oxide nanosheets between the film layers and the active oxygen species excited by light, and the synthesis of the imines is completed in a continuous mobile phase reaction mode, and the product flows out with the mobile phase and leaves the system, simplifying the separation and purification process.
[0005] The object of the present invention is achieved through the following technical solutions: A titanium oxide film catalytic material, wherein the interlayer spacing of the titanium oxide film catalytic material is 1.40nm-1.60nm, and the atomic ratio of titanium to oxygen in the titanium oxide film catalytic material is 0.440-0.465.
[0006] According to an embodiment of the present invention, the titanium oxide film catalytic material has the characteristic of continuously adjustable interlayer spacing of semiconductor properties.
[0007] According to an embodiment of the present invention, the titanium oxide film catalytic material is a titanium oxide film confined catalytic material, which provides an ordered two-dimensional confined channel for the reactants, the interlayer spacing of the titanium oxide film catalytic material is adjustable, and the atomic ratio of titanium and oxygen in the titanium oxide film catalytic material is adjustable; the adjustment of the interlayer spacing can affect the size of the two-dimensional nano-confined channel, the adjustment of the titanium-oxygen atomic ratio can affect the amount of photoexcited active oxygen species, and the adjustment of the synergistic catalytic effect of the two-dimensional nano-confined channel and the active oxygen species can optimize the catalytic performance of the titanium oxide film catalytic material.
[0008] According to an embodiment of the present invention, the interlayer spacing of the titanium oxide film catalyst material is 1.40nm, 1.42nm, 1.45nm, 1.48nm, 1.50nm, 1.52nm, 1.55nm, 1.58nm or 1.60nm. Studies have found that the interlayer spacing can be regulated by regulating the temperature of the heat treatment. The higher the heat treatment temperature, the smaller the interlayer spacing.
[0009] According to an embodiment of the present invention, the atomic ratio of titanium to oxygen in the titanium oxide film catalyst material is 0.440, 0.445, 0.450, 0.455, 0.460 or 0.465. Studies have found that the atomic ratio of titanium to oxygen can be adjusted by adjusting the mixing ratio of titanium dioxide and cesium carbonate, the raw materials for preparing the titanium oxide film catalyst material.
[0010] According to an embodiment of the present invention, the thickness of the titanium oxide film catalytic material is 0.5-10 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm; by regulating the film thickness, the retention time of the reaction molecules in the two-dimensional nano-confined channel of the titanium oxide film catalytic material can be regulated to optimize its catalytic performance. Studies have found that too thin titanium oxide film catalytic materials (thickness less than 0.5 μm) have low mechanical properties and are prone to failure in subsequent catalytic reactions; too thick titanium oxide film catalytic materials (thickness greater than 10 μm) are prone to introduce too many defects, reducing the structural orderliness of the two-dimensional nano-confined channel provided for the reaction molecules, and too thick titanium oxide film catalytic materials (thickness greater than 10 μm) are not easily penetrated by ultraviolet light, and cannot excite the titanium oxide nanosheets above and below the two-dimensional nano-confined channel for photocatalytic reaction.
[0011] The present invention also provides a method for preparing the above titanium oxide film catalytic material, and the method comprises the following steps: (1) Mix titanium dioxide and cesium carbonate, and calcine to prepare cesium titanate in a layered structure; mix the layered cesium titanate with an acid and carry out a protonation reaction to prepare titanic acid; (2) Add the titanic acid to an aqueous solution of tetrabutylammonium hydroxide and carry out a delamination reaction to prepare titanium oxide nanosheets; (3) Assemble the titanium oxide nanosheets into a titanium oxide film by vacuum filtration to prepare the titanium oxide film catalytic material.
[0012] According to an embodiment of the present invention, in step (1), the titanium dioxide is preferably nano-titanium dioxide, for example, nano-titanium dioxide with a particle size of 20-40 nm is selected.
[0013] According to an embodiment of the present invention, in step (1), the source of the titanium dioxide is not particularly defined, and it can be prepared by a method known in the art or obtained by purchasing through commercial channels.
[0014] According to an embodiment of the present invention, in step (1), the mass ratio of the titanium dioxide to the cesium carbonate is 1:0.5-3, for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.5, 1:2.0, 1:2.5 or 1:3.0. By adjusting the mass ratio of the titanium dioxide to the cesium carbonate, cesium titanates (Cs x Ti 2-x / 4 O 4 , 0.6 < x ≤ 1.0) with different compositions can be obtained for preparing titanium oxide film catalytic materials with different atomic ratios of titanium to oxygen; meanwhile, the particle size and crystallinity of the cesium titanate can also be adjusted, so as to obtain a titanium oxide film catalytic material with photocatalytic activity.
[0015] According to an embodiment of the present invention, in step (1), the temperature of the calcination is 600 - 1000 °C, for example, 600 °C, 650 °C, 700 °C, 750 °C, 800 °C, 850 °C, 900 °C, 950 °C or 1000 °C; the time of the calcination is 10 - 40 hours, for example, 10 hours, 12 hours, 15 hours, 16 hours, 20 hours, 24 hours, 30 hours, 36 hours or 40 hours; the heating rate of the calcination is 2 - 10 °C / min, for example, 2 °C / min, 3 °C / min, 5 °C / min, 6 °C / min, 8 °C / min or 10 °C / min; the cooling rate of the calcination is 2 - 10 °C / min, for example, 2 °C / min, 3 °C / min, 5 °C / min, 6 °C / min, 8 °C / min or 10 °C / min; the calcination is carried out in an air atmosphere.
[0016] According to an embodiment of the present invention, in step (1), the number of times of the calcination is 1 - 3 times, for example, 2 times; repeating the calcination multiple times can make the raw materials mix more fully and obtain cesium titanate with higher purity; preferably, after the first calcination ends, the temperature of the calcination product is cooled to room temperature and then ground, and then the second calcination is carried out.
[0017] According to an embodiment of the present invention, in step (1), the chemical formula of the titanium dioxide is TiO 2 。
[0018] According to an embodiment of the present invention, in step (1), the chemical formula of the cesium carbonate is Cs 2 CO 3 。
[0019] According to an embodiment of the present invention, in step (1), the chemical formula of the cesium titanate is Cs x Ti 2-x / 4 O 4 ,0.6 < x ≤ 1.0; exemplarily, the chemical formula of the cesium titanate is Cs 0.7 Ti 1.825 O 4 。
[0020] According to an embodiment of the present invention, in step (1), the chemical formula of the titanic acid is H x Ti 2-x / 4 O 4 ,0.6 < x ≤ 1.0; exemplarily, the chemical formula of the titanic acid is H 0.7 Ti 1.825 O 4 。
[0021] According to an embodiment of the present invention, in step (1), the acid is an inorganic strong acid, such as hydrochloric acid or sulfuric acid; the concentration of the acid is 0.1-3.0 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L or 3.0 mol / L.
[0022] According to an embodiment of the present invention, in step (1), the time of the protonation reaction is 24-96 hours, for example, 48 hours or 72 hours; and the temperature of the protonation reaction is room temperature.
[0023] According to an embodiment of the present invention, in step (2), the concentration of the aqueous solution of tetrabutylammonium hydroxide is 0.001-0.1 mol / L, for example, 0.001 mol / L, 0.002 mol / L, 0.003 mol / L, 0.004 mol / L, 0.005 mol / L, 0.006 mol / L, 0.007 mol / L, 0.008 mol / L, 0.009 mol / L, 0.01 mol / L or 0.1 mol / L.
[0024] According to an embodiment of the present invention, in step (2), the time of the stripping reaction is 3-21 days, for example, 7 days or 14 days; and the temperature of the stripping reaction is room temperature.
[0025] According to an embodiment of the present invention, in step (2), the stripping reaction is carried out under shaking conditions.
[0026] According to an embodiment of the present invention, in step (2), the mass molar ratio of titanic acid to tetrabutylammonium hydroxide is 0.05-1 g / mmol, for example, 0.05 g / mmol, 0.1 g / mmol, 0.15 g / mmol, 0.2 g / mmol, 0.3 g / mmol, 0.4 g / mmol, 0.5 g / mmol, 0.6 g / mmol, 0.7 g / mmol, 0.8 g / mmol, 0.9 g / mmol or 1 g / mmol.
[0027] According to an embodiment of the present invention, in step (2), the titanium oxide nanosheet is preferably a single-layer titanium oxide nanosheet.
[0028] According to an embodiment of the present invention, in step (2), the thickness of the titanium oxide nanosheets is 1.0 nm-1.5 nm, for example, 1.0 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm or 1.5 nm.
[0029] According to an embodiment of the present invention, in step (2), the chemical formula of the titanium oxide nanosheet is Ti y O 2 , 0.93≥y≥0.88; illustratively, the chemical formula of the titanium oxide nanosheet is Ti 0.91 O 2 .
[0030] According to an embodiment of the present invention, in step (3), the thickness of the titanium oxide film catalytic material is 0.5-10 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0031] According to an embodiment of the present invention, step (3) specifically includes the following steps: (3-1) preparing a titanium oxide nanosheet dispersion; (3-2) The titanium oxide nanosheet dispersion of step (3-1) is assembled into a titanium oxide film by vacuum filtration, and then placed in a constant temperature and humidity environment to prepare the titanium oxide film catalytic material.
[0032] According to an embodiment of the present invention, in step (3-1), the concentration of titanium oxide in the titanium oxide dispersion is 0.1-5 mg / mL, for example, 0.1 mg / mL, 0.25 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL or 5 mg / mL.
[0033] According to an embodiment of the present invention, in step (3-1), the titanium oxide dispersion contains titanium oxide nanosheets, tetrabutylammonium hydroxide and deionized water.
[0034] According to an embodiment of the present invention, in step (3-2), the titanium oxide film catalytic material is a layered structure formed by stacking titanium oxide nanosheets.
[0035] According to an embodiment of the present invention, in step (3-2), the titanium oxide dispersion of step (3-1) is added to a filter cup of a vacuum filtration device, and a vacuum pump is started to perform vacuum filtration with a vacuum degree of 1-5 Pa.
[0036] According to an embodiment of the present invention, a porous substrate is laid in the filter cup, that is, a membrane formed by stacking multiple single-layer titanium oxide nanosheets of a certain thickness is prepared on the porous substrate by a vacuum filtration method.
[0037] The porous substrate may be made of an organic filter membrane such as nylon 66, polyvinylidene fluoride, or polytetrafluoroethylene.
[0038] Wherein, the pore size of the porous substrate is 0.1-0.3 μm, for example, 0.22 μm.
[0039] According to an embodiment of the present invention, in step (3-2), as the filtration proceeds, the titanium oxide nanosheets in the titanium oxide dispersion are assembled into a layered structure under the action of water flow, and when the filtration is completed, the titanium oxide film catalytic material is obtained.
[0040] According to an embodiment of the present invention, in step (3-2), the constant temperature and humidity static treatment is, for example, static treatment for a period of time under constant temperature and constant humidity conditions, such as in a constant temperature and humidity chamber. Exemplarily, static treatment is performed at 20-25°C and 5-20RH% for 2-12 hours.
[0041] According to an embodiment of the present invention, in step (3-2), the constant temperature and humidity static treatment can achieve the removal of free water in the titanium oxide film after the filtration is completed.
[0042] According to an embodiment of the present invention, the method further comprises the following steps: (4) Heat treating the titanium oxide film catalyst material of step (3).
[0043] According to an embodiment of the present invention, in step (4), the heat treatment time is 8-16 hours, for example, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours or 16 hours; the heat treatment temperature is 40-120°C, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C. Too low heat treatment temperature (<40°C) is not conducive to water loss and cannot effectively regulate the interlayer spacing of the titanium oxide film catalyst material; too high heat treatment temperature (>120°C) will cause the titanium oxide to denature, which is not conducive to maintaining the intrinsic chemical structure of the titanium oxide film catalyst material, and will also increase the mass transfer resistance of the titanium oxide film catalyst material, affecting the fluidity of the reactant molecules.
[0044] According to an embodiment of the present invention, in step (4), the heat treatment is performed in a vacuum oven.
[0045] According to an embodiment of the present invention, in step (4), the heat treatment can remove part of the bound water existing between the layers of the titanium oxide film catalyst material, which can effectively regulate the interlayer spacing of the titanium oxide film catalyst material to obtain a titanium oxide film catalyst material with continuously adjustable interlayer spacing.
[0046] The present invention also provides a titanium oxide film catalytic material prepared by the method.
[0047] The present invention also provides the use of the titanium oxide film catalytic material, which is used for photocatalytic coupling of benzylamine compounds to prepare imines.
[0048] According to the embodiment of the present invention, the titanium oxide film catalytic material is used for rapid photocatalytic coupling of benzylamine compounds to prepare imines.
[0049] According to an embodiment of the present invention, the titanium oxide film catalytic material is used for fast and high-yield photocatalytic coupling of benzylamine compounds to prepare imines.
[0050] According to an embodiment of the present invention, the fast refers to a reaction time range of 0.1-100s, for example, 0.1s, 0.2s, 0.3s, 0.4s, 0.5s, 0.6s, 0.7s, 0.8s, 0.9s, 1s, 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s, 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s or 100s.
[0051] According to an embodiment of the present invention, the high yield refers to a reaction yield range of 70-100%, for example, 70%, 75%, 80%, 85%, 90%, 95% or 100%.
[0052] According to an embodiment of the present invention, the coupling of benzylamine compounds to prepare imines is carried out in a continuous mobile phase reaction under ultraviolet light irradiation and driven by pressure difference. The benzylamine compounds react in the two-dimensional nano-confined channel of the titanium oxide film catalytic material, and the product imine flows out with the mobile phase and leaves the system.
[0053] The present invention also provides a method for preparing imines by photocatalytic coupling of benzylamine compounds, the method comprising the following steps: (1) dissolving a benzylamine compound in an organic solvent to obtain a membrane reaction solution; (2) The cross-membrane reaction solution is driven by pressure difference and passes through the titanium oxide film catalyst material under the irradiation of ultraviolet light to carry out a photocatalytic coupling reaction of benzylamine compounds.
[0054] According to an embodiment of the present invention, in step (1), the concentration of the benzylamine compound in the transmembrane reaction solution is 0.01-5 mol / L, for example, 0.01 mol / L, 0.02 mol / L, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L or 5 mol / L.
[0055] According to an embodiment of the present invention, in step (1), the organic solvent is a polar solvent, such as acetonitrile.
[0056] According to an embodiment of the present invention, in step (1), the benzylamine compound is selected from benzylamine and its ortho-, meta- and para-substituted homologues; illustratively, the benzylamine compound is selected from at least one of benzylamine, 2-methylbenzylamine, 3-methylbenzylamine, 4-methylbenzylamine, 2-trifluoromethylbenzylamine, 3-trifluoromethylbenzylamine, 4-trifluoromethylbenzylamine, 2-methoxybenzylamine, 3-methoxybenzylamine, 4-methoxybenzylamine, 2-tert-butylbenzylamine, 3-tert-butylbenzylamine, 4-tert-butylbenzylamine, 2,3-difluorobenzylamine, 2,4-difluorobenzylamine, 2,3-dichlorobenzylamine, 2,4-dichlorobenzylamine, 2,3-dibromobenzylamine, 2,4-dibromobenzylamine, 2-fluorobenzylamine, 3-fluorobenzylamine, 4-fluorobenzylamine, 2-chlorobenzylamine, 3-chlorobenzylamine, 4-chlorobenzylamine, 2-bromobenzylamine, 3-bromobenzylamine and 4-bromobenzylamine.
[0057] According to an embodiment of the present invention, in step (2), the reaction time is 0.1-100 s.
[0058] According to an embodiment of the present invention, in step (2), no additional heat source needs to be introduced during the photocatalytic coupling reaction of benzylamine compounds, that is, no additional heating treatment is required during the reaction.
[0059] According to an embodiment of the present invention, in step (2), the photocatalytic coupling reaction of benzylamine compounds is carried out under an air atmosphere, that is, no additional oxygen needs to be introduced during the reaction.
[0060] According to an embodiment of the present invention, in step (2), the method for generating the ultraviolet light is not particularly limited, as long as ultraviolet light can be obtained, for example, the surface of the titanium oxide film catalyst material can be irradiated by an LED ultraviolet lamp.
[0061] According to an embodiment of the present invention, in step (2), the intensity of the ultraviolet light is 61-412 mW / cm -2 .
[0062] According to an embodiment of the present invention, in step (2), the method for generating the pressure difference is not particularly limited, and for example, negative pressure may be generated on the lower surface of the titanium oxide film catalyst material by vacuum filtration, and / or positive pressure may be generated on the upper surface of the titanium oxide film catalyst material by external pressure.
[0063] Exemplarily, the pressure difference is achieved by vacuum filtration, for example, by adding the transmembrane reaction solution to a vacuum filtration device provided with a titanium oxide film catalytic material, starting a vacuum pump, and performing vacuum filtration to generate a pressure difference between the upper and lower surfaces of the titanium oxide film catalytic material.
[0064] According to an embodiment of the present invention, in step (2), the pressure difference is not particularly limited, such as being greater than 0.5 atm. Exemplarily, the pressure difference is 0.5-1.0 atm, such as 0.8-1.0 atm, such as 0.5 atm, 0.6 atm, 0.7 atm, 0.8 atm, 0.9 atm or 1.0 atm.
[0065] According to an embodiment of the present invention, in step (2), the yield of the reaction is 70-100%.
[0066] Beneficial effects of the present invention: The present invention is based on the concept of confined flow chemical reaction in an artificial system, and utilizes the intrinsic semiconductor charge separation photocatalytic properties provided by two-dimensional nano-element materials titanium oxide nanosheets and the synergistic catalytic effect of two-dimensional nano-confined channels provided after the two-dimensional nano-element materials are assembled into macroscopic films, thereby reducing the molecular freedom of reactants and the disordered diffusion caused by thermal motion in the solution, reducing the activation energy of the chemical reaction, and changing the chemical reaction path, thereby realizing rapid and high-yield photocatalytic coupling of benzylamine compounds to prepare imines.
[0067] The titanium oxide film catalytic material of the present invention has semiconductor properties and can produce active oxygen species under ultraviolet light excitation. The titanium oxide film catalytic material has a narrow band gap and can effectively promote charge separation. Combined with the two-dimensional nano-confined channels provided between the titanium oxide film catalytic material layers, the freedom of the reactant molecules is reduced, so that the molecules break bonds and form bonds in a specific orientation, ensuring that the molecules pass through the confined channels in an orderly manner, reducing the reaction activation energy and changing the reaction path. Therefore, this confined catalytic mechanism based on the artificial system will greatly improve the catalytic effect of the catalyst.
[0068] The present invention adjusts the interlayer spacing, active oxygen species content and reaction time of the titanium oxide film catalytic material by changing the heat treatment temperature, light intensity and film thickness, optimizes the compatibility of the reaction system and reactant molecules for preparing imines by coupling of confined photocatalytic benzylamine compounds, and significantly improves the catalytic effect of the titanium oxide film catalytic material.
[0069] The titanium oxide film catalytic material of the present invention can be used for rapid and high-yield photocatalytic coupling of benzylamine compounds to prepare imines. The reactants react in the two-dimensional nano-confined channels between the titanium oxide film catalytic material layers in a continuous mobile phase reaction mode, and the product imine flows out with the mobile phase, thereby achieving rapid (0.1-100s) and high-yield (70-100%) synthesis of imines and simplifying the separation and purification process. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 : A flow chart of the preparation process of titanium oxide film catalytic material described in a preferred embodiment of the present invention.
[0071] Figure 2: An optical photograph of the titanium oxide film catalytic material described in a preferred embodiment of the present invention.
[0072] Figure 3 : A scanning electron microscope image of the titanium oxide film catalytic material described in a preferred embodiment of the present invention.
[0073] Figure 4 : A process flow chart of preparing imines by photocatalytic coupling of benzylamine compounds using titanium oxide film catalyst material as described in a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0074] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0075] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0076] In the following examples and comparative examples, unless otherwise specified, "TO aqueous solution" refers to "titanium oxide nanosheet dispersion".
[0077] In the following embodiments and comparative examples, unless otherwise specified, "TO film" refers to "titanium oxide film catalytic material".
[0078] In the following embodiments and comparative examples, unless otherwise specified, "TTO membrane" refers to "heat-treated titanium oxide membrane catalytic material".
[0079] In the following embodiments and comparative examples, the permeation product is quantitatively analyzed by gas chromatography to calculate the reaction yield, which specifically includes the following steps: after the reaction is completed, ethanol is added to the filter bottle to obtain a product collection liquid, and a portion of the product collection liquid is taken into a chromatographic injection bottle to obtain a gas chromatography sample. Different substances have different characteristic retention times in a gas chromatograph, and there is a corresponding relationship between the peak area at the characteristic retention time and the mass of the substance, and then the molar amount of the substance can be calculated, and the reaction yield is calculated by the ratio of the corresponding molar amounts.
[0080] Example 1 (1) 4.6 g of cesium carbonate (Cs 2 CO 3 ) and 5.98g nano titanium dioxide (TiO 2 ) were mixed and ground, and then calcined at 800°C for 20 hours; the grinding and calcination were repeated twice to obtain cesium titanate (Cs 0.7 Ti 1.825 O4 ); Place cesium titanate powder in 1 mol / L hydrochloric acid for 72 hours, and replace the hydrochloric acid every 24 hours, and filter to obtain titanate (H 0.7 Ti 1.825 O 4 ·H 2 O) solid, and washed with deionized water for 3 times and then air-dried for use.
[0081] Take 1g of titanate solid powder, add it to 250mL of 0.04mol / L tetrabutylammonium hydroxide aqueous solution, and shake it mechanically for 14 days; dilute it with water to obtain a 2.0mg / mL TO aqueous solution, which is stored for later use.
[0082] (2) Take 0.5 mL of the prepared TO aqueous solution, add deionized water to dilute it to 25 mL, and then assemble it into a TO membrane by vacuum filtration. After the water on the membrane is drained, remove the TO membrane from the filtration device, place it in a watch glass, and place it in a constant temperature and humidity chamber at 25°C and 15RH% for 12 hours to obtain a TO membrane. The thickness of the obtained TO membrane is 2.50 μm, the atomic ratio of titanium to oxygen is 0.45, and the interlayer spacing is 1.58 nm.
[0083] (3) Using TO film as a catalyst, at 412mW / cm -2 The coupling reaction of benzylamine was catalyzed under ultraviolet light. The specific operation was as follows: the TO membrane was purged with nitrogen to remove the dust on the surface, and it was fixed and a sealing gasket was installed to ensure that it was sealed in the micro-filtration device; then the membrane reaction solution was prepared: 25 mL of acetonitrile was added with 0.5 mmol of benzylamine and mechanically stirred for 10 min; then 5 mL of the above membrane reaction solution was added to the columnar filter cup above the filtration device. Driven by the pressure difference (~1 atm), the membrane reaction solution passed through the interlayer two-dimensional nano-confined channel of the TO membrane, and 412 mW / cm was applied above the TO membrane. -2 Under ultraviolet light, the reactant benzylamine undergoes a photocatalytic reaction between the layers of the TO membrane, and the product imine flows out with acetonitrile. Add ethanol to the bottom triangular liquid collection filter bottle to dissolve the product, take part of the collected liquid into the chromatographic injection bottle, analyze the components by gas chromatography, and calculate the reaction yield.
[0084] Reaction results: reaction time was 6.62s and yield was 99%.
[0085] Comparative Example 1 (1) Same as step (1) of Example 1.
[0086] (2) Take 0.5 mL of the prepared TO aqueous solution in a centrifuge tube, immerse it in liquid nitrogen and freeze it, then freeze-dry it for 48 hours to obtain TO powder, and then place it in a constant temperature and humidity chamber at 25°C and 15RH% for 12 hours to obtain TO powder; then prepare the reaction solution: take 25 mL of acetonitrile, add 0.5 mmol of benzylamine, and stir it mechanically for 10 minutes; take 5 mL of the above reaction solution and TO powder, add them to a glass bottle, stir it mechanically for 10 minutes, and apply 412 mW / cm above the glass bottle. -2 UV light, 6 hours after the reaction started, sample 0.1 mL from the reaction solution into a chromatographic injection bottle, add 0.9 mL of ethanol to dilute, analyze the components by gas chromatography, and calculate the reaction yield.
[0087] Reaction results: The reaction time was 6 hours and the yield was 49%.
[0088] Example 2 Other operations are the same as those in Example 1, except that: The TO film was placed in a constant temperature and humidity chamber at 25°C and 15 RH% for 12 hours in step (2) and then transferred to an oven for heat treatment at 40°C for 12 hours to obtain a TTO film. The interlayer spacing of the obtained TTO film was 1.51 nm. The TTO film was used as a catalyst at 310 mW / cm -2 The coupling reaction of benzylamine was catalyzed under ultraviolet light, and the specific process was shown in Example 1. Reaction results: the reaction time was 5.79 s, and the yield was 81%.
[0089] Example 3-1 Other operations are the same as those in Example 1, except that: (2) Take 0.42 mL of the prepared TO aqueous solution, add deionized water to dilute it to 25 mL, and then assemble it into a TO membrane by vacuum filtration. After the water above the membrane is drained, remove the TO membrane from the filtration device, place it in a watch glass, and place it in a constant temperature and humidity chamber maintained at 25°C and 15RH% for 12 hours.
[0090] (3) The thickness of the obtained TO film is 2.08 μm, the atomic ratio of titanium to oxygen is 0.45, and the interlayer spacing is 1.58 nm. The TO film is used as a catalyst at 412 mW / cm -2 Benzylamine is catalyzed to undergo a coupling reaction under ultraviolet light irradiation, and the specific process is shown in Example 1.
[0091] Reaction results: reaction time was 5.79s and yield was 98%.
[0092] Example 3-2 Other operations are the same as those in Example 1, except that: (2) Take 0.33 mL of the prepared TO aqueous solution, add deionized water to dilute it to 25 mL, and then assemble it into a TO membrane by vacuum filtration. After the water above the membrane is drained, remove the TO membrane from the filtration device, place it in a watch glass, and place it in a constant temperature and humidity chamber maintained at 25°C and 15RH% for 12 hours.
[0093] (3) The thickness of the obtained TO film is 1.67 μm, the atomic ratio of titanium to oxygen is 0.45, and the interlayer spacing is 1.58 nm. The TO film is used as a catalyst at 412 mW / cm -2 Benzylamine is catalyzed to undergo a coupling reaction under ultraviolet light irradiation, and the specific process is shown in Example 1.
[0094] Reaction results: reaction time was 3.09s and yield was 95%.
[0095] Example 3-3 Other operations are the same as those in Example 1, except that: (2) Take 0.25 mL of the prepared TO aqueous solution, add deionized water to dilute it to 25 mL, and then assemble it into a TO membrane by vacuum filtration. After the water above the membrane is drained, remove the TO membrane from the filtration device, place it in a watch glass, and place it in a constant temperature and humidity chamber maintained at 25°C and 15RH% for 12 hours.
[0096] (3) The thickness of the obtained TO film is 1.25 μm, the atomic ratio of titanium to oxygen is 0.45, and the interlayer spacing is 1.58 nm. The TO film is used as a catalyst at 412 mW / cm -2 Benzylamine is catalyzed to undergo a coupling reaction under ultraviolet light irradiation, and the specific process is shown in Example 1.
[0097] Reaction results: reaction time was 1.63s and the yield was 83%.
[0098] Embodiment 3-4 Other operations are the same as those in Example 1, except that: (2) Take 0.17 mL of the prepared TO aqueous solution, add deionized water to dilute it to 25 mL, and then assemble it into a TO membrane by vacuum filtration. After the water above the membrane is drained, remove the TO membrane from the filtration device, place it in a watch glass, and place it in a constant temperature and humidity chamber maintained at 25°C and 15RH% for 12 hours.
[0099] (3) The thickness of the obtained TO film is 0.83 μm, the atomic ratio of titanium to oxygen is 0.45, and the interlayer spacing is 1.58 nm. The TO film is used as a catalyst at 412 mW / cm -2 Benzylamine is catalyzed to undergo a coupling reaction under ultraviolet light irradiation, and the specific process is shown in Example 1.
[0100] Reaction results: reaction time was 1.39s and yield was 75%.
[0101] Example 4-1 Other operations are the same as those in Example 1, except that: Using TO film as catalyst, at 412mW / cm -2 It catalyzes the coupling reaction of 4-methylbenzylamine under ultraviolet light.
[0102] Reaction results: reaction time was 6.77s and the yield was 98%.
[0103] Example 4-2 Other operations are the same as those in Example 1, except that: Using TO film as catalyst, at 412mW / cm -2 It catalyzes the coupling reaction of 3-methylbenzylamine under ultraviolet light.
[0104] Reaction results: reaction time was 6.62s and yield was 98%.
[0105] Example 4-3 Other operations are the same as those in Example 1, except that: Using TO film as catalyst, at 412mW / cm -2 Under ultraviolet light, 4-chlorobenzylamine was catalyzed to undergo coupling reaction.
[0106] Reaction results: reaction time was 4.79s and yield was 96%.
[0107] Example 4-4 Other operations are the same as those in Example 1, except that: Using TO film as catalyst, at 412mW / cm -2 Under ultraviolet light, 3-chlorobenzylamine was catalyzed to undergo coupling reaction.
[0108] Reaction results: reaction time was 6.26s and yield was 97%.
[0109] Embodiment 4-5 Other operations are the same as those in Example 1, except that: Using TO film as catalyst, at 412mW / cm -2 Under ultraviolet light, it catalyzes the coupling reaction of 4-methoxybenzylamine.
[0110] Reaction results: reaction time was 8.34s and yield was 98%.
[0111] Embodiment 4-6 Other operations are the same as those in Example 1, except that: Using TO film as catalyst, at 412mW / cm -2 Under ultraviolet light, it catalyzes the coupling reaction of 4-bromobenzylamine.
[0112] Reaction results: reaction time was 7.42s and the yield was 98%.
[0113] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A titanium oxide film catalytic material, characterized in that: The interlayer spacing of the titanium oxide film catalyst material is 1.40nm-1.60nm, and the atomic ratio of titanium to oxygen in the titanium oxide film catalyst material is 0.440-0.
465.
2. The titanium oxide film catalytic material according to claim 1, characterized in that: The thickness of the titanium oxide film catalytic material is 0.5-10 μm.
3. The method for preparing the titanium oxide film catalyst material according to claim 1 or 2, the method comprising the following steps: (1) titanium dioxide and cesium carbonate are mixed and calcined to prepare layered cesium titanate; the layered cesium titanate is mixed with an acid and subjected to a protonation reaction to prepare titanic acid; (2) adding titanic acid to an aqueous solution of tetrabutylammonium hydroxide to carry out an exfoliation reaction to prepare titanium oxide nanosheets; (3) Assembling titanium oxide nanosheets into titanium oxide membranes by vacuum filtration to obtain the titanium oxide membrane catalytic material.
4. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of titanium dioxide to cesium carbonate is 1:0.5-3; And / or, in step (1), the calcination temperature is 600-1000°C; the calcination time is 10-40 hours; And / or, in step (1), the chemical formula of the cesium titanate is Cs x Ti 2-x / 4 O4, 0.6 <x≤1.0; And / or, in step (1), the chemical formula of the titanic acid is H x Ti 2-x / 4 O4, 0.6 <x≤1.0; And / or, in step (2), the mass molar ratio of titanic acid to tetrabutylammonium hydroxide is 0.05-1 g / mmol; And / or, in step (2), the chemical formula of the titanium oxide nanosheet is Ti y O2, 0.93≥y≥0.
88.
5. The preparation method according to claim 3 or 4, characterized in that: The method further comprises the steps of: (4) Heat treating the titanium oxide film catalyst material of step (3).
6. The preparation method according to claim 5, characterized in that: In step (4), the heat treatment time is 8-16 hours; the heat treatment temperature is 40-120°C.
7. The titanium oxide film catalytic material prepared by the method according to any one of claims 3 to 6.
8. Use of the titanium oxide film catalytic material according to any one of claims 1 to 2 and 7 for photocatalytic coupling of benzylamine compounds to prepare imines.
9. A method for preparing imines by photocatalytic coupling of benzylamine compounds, the method comprising the following steps: (1) dissolving a benzylamine compound in an organic solvent to obtain a membrane reaction solution; (2) The cross-membrane reaction solution is driven by pressure difference and subjected to ultraviolet light to pass through the titanium oxide film catalytic material according to any one of claims 1 to 2 and 7 to perform a photocatalytic coupling reaction of benzylamine compounds.
10. The method according to claim 9, characterized in that In step (1), the concentration of the benzylamine compound in the transmembrane reaction solution is 0.01-5 mol / L; and / or, in step (1), the benzylamine compound is selected from at least one of benzylamine, 2-methylbenzylamine, 3-methylbenzylamine, 4-methylbenzylamine, 2-trifluoromethylbenzylamine, 3-trifluoromethylbenzylamine, 4-trifluoromethylbenzylamine, 2-methoxybenzylamine, 3-methoxybenzylamine, 4-methoxybenzylamine, 2-tert-butylbenzylamine, 3-tert-butylbenzylamine, 4-tert-butylbenzylamine, 2,3-difluorobenzylamine, 2,4-difluorobenzylamine, 2,3-dichlorobenzylamine, 2,4-dichlorobenzylamine, 2,3-dibromobenzylamine, 2,4-dibromobenzylamine, 2-fluorobenzylamine, 3-fluorobenzylamine, 4-fluorobenzylamine, 2-chlorobenzylamine, 3-chlorobenzylamine, 4-chlorobenzylamine, 2-bromobenzylamine, 3-bromobenzylamine and 4-bromobenzylamine; And / or, in step (2), the reaction time is 0.1-100 s; And / or, in step (2), the pressure difference is 0.5-1.0 atm.
Citation Information
Patent Citations
Compound desalination membrane as well as preparation method and application thereof
CN104607069A
Ultrathin two-dimensional titanium oxide nanosheet material with large specific surface and preparing method
CN109133162A
Preparation method of nanowire catalytic ceramic membrane with high flux and visible light response
CN114471511A
Preparation and application of mineral functional membrane coupled with advanced oxidation technology
CN117323842A
Titanium oxide film, liquid and process for forming the same and photocatalytic member
JP2004155608A
